Molybdenum(v)-mediated switching of the C(sp2)-Se bond of phenylselenyl-functionalized arenes or heterocycles under mild conditions - Zhang, Ming; Nian, Beifang; Wu, Zhibang; Guo, Jianhua; Chen, Zhuo; Yuan, Caifeng; Huang, Xuankun; Shen, Yiwen; Zhang, Hongbin; Tang, E. (Chemical communications (Cambridge, England), 2023)
Molybdenum(v)-mediated cleavage of C(sp(2))-Se bond and C(sp(2))-H bond as well as intramolecular oxidative C(sp(2))-Se coupling reaction of phenylselenyl-functionalized arenes or heterocycles has been developed. Three kinds of benzoselenophene frameworks were constructed through this reaction with yields up to 94%. This new C(sp(2))-Se bond-switching methodology may provide a new strategy for interesting applications of phenylselenyl-substituted aromatic compounds in the synthesis of selenium-containing heterocycles and natural products.